Kinematic Design of Rice Seed Planting Tool Using Four Bars Linkage Mechanism - Rozi Saferi; Asmara Yanto; M Aldi Putra (Jurnal Teknik Mesin, 2021)
Kinematics is the study of the relative motion of a component which includes the speed and acceleration of a machine without considering the causes of motion. The planting arm on the semi-mechanical rice seed planting tool works as a component of taking and planting rice into the soil. The planter arm is made using a four-bars linkage mechanism. The purpose of this research is to analyze the effect of kinematic parameters on the mechanism and to design the setting of planting depth by varying the length of the bars and calculating the speed and acceleration of the finger of the planter. The method used in this research is done analytically with GIM software application. The result of this research is the design of the dimensions of 4 bars linkage and the input value given to link 2 will affect the distance and depth of planting of rice using seed planting tool. Based on the dimensions and input values given, the planting depth is in the range of 83 mm so that it has met the required seedling planting criteria.